Dedicated instruments for nano-engineering education: Integrated nano-manipulation and micro-nanomachining. Issue 1 (January 2021) - Mekid, Samir
Introducing Nanotechnology course with extensive lab experiments to engineering students becomes essential during their undergraduate studies. It is believed that Nanotechnology should be defined in a specific track within the undergraduate engineering curriculum. The current practice shows several universities adopting this course but with different approaches. The paper exhibits two new instruments designed to support micro/nano-technology education for engineering students. An integrated nano-manipulator and micro-machining instruments have been designed with various operations to allow more capabilities offered to students to acquire hands-on experience in labs. The students' activities are planned to follow a planned set of units describing experimental activities and designed for the students as a roadmap for a couple of weeks, or the students' ideas as free access after a training. With integrated functions, the instruments would allow more freedom to students to explore and investigate their curiosity.